Longer respiratory events in childhood obstructive sleep apnea syndrome constitute a trait of older children with excessive daytime sleepiness - Plamen Bokov; Benjamin Dudoignon; Boris Matrot; Christophe Delclaux (Scientific Reports)
Abstract The objective was to evaluate the determinants of desaturation during apnea and apnea–hypopnea duration’s links with the endotypes (pharyngeal compliance, loop gain) of obstructive sleep apnea (OSA) and with heart rate variability (HRV) indices. We retrospectively selected 35 otherwise healthy children (median age: 10.6 years, 16 females) with moderate to severe OSA who had measurements of pharyngeal compliance (acoustic pharyngometry), loop gain (awake tidal ventilation with calculation of controller and plant gains), and respiratory system impedance (impulse oscillometry system). HRV indices were obtained from the whole-night ECG of polysomnography. The slope of desaturation (0.64%.s−1) during apnea was related to baseline end-tidal PO2 (r2 = 0.74; p < 0.001), which is influenced by small airway disease (reactance at 5 Hz and its area). The mean durations of apnea and hypopnea in NREM and REM sleep were combined into the mean apnea–hypopnea duration (MAD4), which positively correlated with age, sleepiness, and HRV indices. The MAD4 correlated with two endotypic traits, controller and plant gains. In conclusion, arterial desaturation during apnea is related to alveolar PO2. Longer respiratory events constitute a trait of older children with excessive daytime sleepiness, higher HRV, and adaptive responses of ventilatory control to maintain its stability.